Accurate endoscopic identification of the afferent limb at the Y anastomosis using the fold disruption sign after gastric resection with Roux‐en‐Y reconstruction. Issue 1 (12th October 2021) - Kanno, Yoshihide; Ohira, Tetsuya; Kozakai, Fumisato; Miyamoto, Kazuaki; Kusunose, Hiroaki; Sakai, Toshitaka; Yonamine, Keisuke; Okano, Haruka; Koshita, Shinsuke; Ogawa, Takahisa; Shimizu, Takeshi; Ito, Kei
Abstract : In patients with Roux‐en‐Y (RY) reconstruction for gastric resection, the newly defined "fold disruption" (FD) sign can be useful to distinguish the afferent limb from the efferent limb at the Y anastomosis when balloon endoscopy‐assisted endoscopic retrograde cholangiopancreatography (BE‐ERCP) is performed. The FD sign was defined as endoscopic findings of the internal folds disrupted toward the afferent limb and continued toward the efferent limb at the Y anastomosis. In this prospective observational study, the accuracy of the FD sign was evaluated for those who underwent BE‐ERCP after gastric resection with RY reconstruction. Of 28 patients for whom the accuracy could be evaluated among 30 enrolled patients, the afferent limb was identified using the FD sign with 100% accuracy. For the other two patients, the scope could not reach the target lumen due to severe intestinal adhesion in one and reached the target lumen without recognition of the Y anastomosis in the other. There was no patient for whom the FD sign could not be judged for any reason, such as a blurred anastomosis line, unclear folds, sticky discharge and blood coating the surface, when the Y anastomosis was recognized. The FD sign was a highly accurate tool for distinguishing the afferent limb from the efferent limb in patients after gastric resection with RY reconstruction. This study was registered in UMIN (issued ID, UMIN000038326).